Carbon-coated double-active-site nitrogen-doped carbon-based catalyst as well as preparation method and application thereof

By using carbon-coated dual active site nitrogen-doped carbon-based catalysts in hydrothermal oxidation technology, the problem of difficult degradation of extracellular polymers in sludge is solved, achieving deep cracking of sludge and efficient resource utilization of organic matter. use.

CN119346117APending Publication Date: 2025-01-24HANGZHOU SHENRUI WATER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411477412.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing hydrothermal oxidation technology cannot effectively degrade extracellular polymers in the sludge, resulting in the sludge treated with sludge still containing high organic matter and the carbon source recovery is not thorough.

Method used

The carbon -covered dual -active position nitrogen doped carbon -based catalysts are used to further solve the extracellular polymer in the sludge through the hydrophilic oxidation reaction, and improve the carboxylic acid product selectivity of the organic matter.

Benefits of technology

It significantly improves the degree of sludge, enables more organic substances to enter the liquid phase, improves the selectivity of carboxylic acid products, realizes the deep cracking and resource utilization of sludge, and maintains catalytic activity in high -salt environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346117A_ABST
    Figure CN119346117A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon-coated double-active-site nitrogen-doped carbon-based catalyst as well as a preparation method and application thereof, the catalyst comprises nitrogen-doped carbon spheres loaded by two active metals and a carbon coating layer, and metal active components comprise a first metal selected from Fe, Mn and Cu and a second metal Ni; nitrogen is doped in the carrier, so that a defect structure can be formed in the carbon material, abundant acid-base sites are provided, the oxidation reaction activity is improved, the cracking degree of sludge extracellular polymeric substances is further improved, deep cracking of sludge is realized, and the selectivity of organic matter carboxylic acid products is improved; the metal particles on the surface of the catalyst can further improve the catalytic activity, the synergistic effect between the defect structure and the active metal can control the oxidation degree, the selectivity of C1-C2 carboxylic acid products is improved, and the carbon coating structure on the outer side of the catalyst can provide a protection effect for the active metal on the premise of not influencing the activation of the oxidizing agent; according to the catalyst, sludge HTO resourceful treatment under the condition of 200 DEG C or below can be achieved, and the stability of the catalyst in a complex environment, especially in a high-salt system is effectively improved while the efficient catalytic performance is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of hydrothermal oxidation sludge treatment catalysts, and in particular to a carbon-coated dual-active site nitrogen-doped carbon-based catalyst and a preparation method and application thereof. Background Art

[0002] With the advancement of urbanization in my country, the scale of urban sewage has increased dramatically. The biological treatment of urban sewage in my country mainly uses the activated sludge method. The mechanism of activated sludge treatment of sewage is as follows: in the sewage treatment process, the bacterial flocs oxidize and decompose various organic matter in the wastewater into carbon dioxide and water, and generate flocs at the same time. At this time, the microbial group of activated sludge is formed. The activated sludge absorbs some pollutants in the sewage and flocculates and settles, producing a large amount of residual sludge.

[0003] Sludge is mainly composed of sludge flocs and water. Sludge flocs are mainly composed of two parts: cell bodies and extracellular polymers. Extracellular polymers are mainly composed of proteins and polysaccharides. Polysaccharide molecules are rich in hydrophilic functional groups such as hydroxyl and carboxyl groups. They can form a stable and elastic network structure through adsorption and bridging, and cross-linking and fixing free cells is beneficial to sludge flocculation. Proteins and lipids can maintain the stability of the floc structure and improve the biological flocculation of sludge accordingly. Polysaccharide molecules, proteins and lipids form a compact and dense network structure through electrostatic forces, hydrogen bonding, ion attraction, biochemistry and other effects, which can serve as a protective layer for microorganisms to resist the invasion of adverse factors such as external heavy metals and toxic compounds. Therefore, the presence of extracellular polymers is also the main reason for the difficulty in sludge degradation. At the same time, the various forces inside / between extracellular polymers make the water in the sludge tightly bound inside / between the sludge flocs through adsorption or chemical bonds, which ultimately leads to a high moisture content in the sludge and is not easy to dehydrate.

[0004] The problem of residual sludge generated during the sewage treatment process is becoming increasingly serious. Data show that my country's sludge production reached 72.883 million tons in 2020, and only about 10% of these sludges were returned to the land after anaerobic digestion and composting, about 20% were sanitary landfilled, incinerated and used as building materials, and most of the rest were not properly disposed of. The residual sludge has a high moisture content, large volume, and a foul odor. It also contains a large number of pathogens, heavy metals and other toxic substances. Improper treatment can easily cause serious secondary environmental pollution. Traditional sludge treatment technologies include anaerobic digestion, dehydration, landfill, incineration, etc. However, traditional sludge treatment technologies have fatal problems such as high cost and secondary pollution, and cannot achieve resource utilization of sludge.

[0005] Hydrothermal Oxidation (HTO) is widely used in the field of organic wastewater and solid waste treatment due to its green and efficient advantages. The reaction with an oxidant in an aqueous solution under high temperature and high pressure conditions in a closed system is a hydrothermal oxidation reaction. Hydrothermal oxidation conditions can effectively release the water component in the sludge, and at the same time break the cell structure in the sludge, thereby releasing the organic matter in it and dissolving it in the liquid phase, thereby achieving sludge stabilization, harmlessness and reduction. In addition, the released organic matter is dissolved in the supernatant, and a large amount of soluble organic matter is oxidized and degraded into volatile fatty acids VFAs and other organic matter such as carbohydrates and proteins under oxygen-rich conditions, which can be used as substrates for the metabolism of various microorganisms. It is a high-quality carbon source and realizes resource utilization. However, the existing HTO technology cannot effectively degrade the extracellular polymers of the sludge, resulting in a low degree of degradation of the extracellular polymers of the sludge, and thus cannot achieve deep decomposition of the sludge, resulting in a high content of organic matter in the treated sludge and incomplete carbon source recovery. Summary of the invention

[0006] The present invention provides a carbon-coated dual-active site nitrogen-doped carbon-based catalyst and a preparation method and application thereof to solve the above problems.

[0007] In order to achieve the above object, the technical solution of the present invention is:

[0008] In one aspect, the present invention provides a carbon-coated dual-active-site nitrogen-doped carbon-based catalyst, wherein the catalyst comprises: the carbon-coated dual-active-site nitrogen-doped carbon-based catalyst comprises two active metal-supported nitrogen-doped carbon balls and a carbon coating layer; the thickness of the carbon coating layer is 0.2 to 0.4 nm;

[0009] The metal active component includes a first metal and a second metal, wherein the first metal is one of transition metals Fe, Mn, and Cu, and the second metal is metal Ni.

[0010] Further, the loading amount of the first metal is 1 to 10 wt%;

[0011] The mass ratio of the first metal to the second metal is 10 to 20:1.

[0012] Furthermore, the carrier precursor of the nitrogen-doped carbon spheres is waste resin.

[0013] Another aspect of the present invention provides a method for preparing a carbon-coated dual-active site nitrogen-doped carbon-based catalyst, comprising the following steps:

[0014] S1: dissolving 10-50 g of a nitrate containing a first metal and 1-10 g of a nitrate containing a second metal in 110 mL of deionized water to obtain a mixed solution, adding 100 g of waste resin as a precursor to the mixed solution, then adding a nitrogen source, and ultrasonicating for 15-30 min to obtain a mixture;

[0015] S2: The mixture after ultrasound was dried, calcined and naturally cooled to obtain a carbon-coated dual-active site nitrogen-doped carbon-based catalyst.

[0016] Furthermore, the nitrogen source is selected from at least one of urea and dicyandiamide powder, and the mass ratio of the nitrogen source to the waste resin precursor is 1 to 5:1.

[0017] Furthermore, in S2, the drying conditions are: drying at a temperature of 103-105° C. for 3-6 hours.

[0018] Furthermore, in S2, the calcination conditions are: the dried product is calcined at 600-1000° C. for 2 h under an inert atmosphere, and the temperature program is set at 1-5° C. / min.

[0019] On the other hand, the present invention provides the use of a carbon-coated dual-active site nitrogen-doped carbon-based catalyst described in the above technical scheme or a carbon-coated dual-active site nitrogen-doped carbon-based catalyst prepared by the preparation method described in the above technical scheme in treating residual sludge to produce carboxylic acid carbon sources.

[0020] Furthermore, the application is carried out in a device for hydrothermal oxidation of excess sludge, the device for hydrothermal oxidation of excess sludge comprising a raw sludge transmission system, a reaction tower, a heat exchange unit and a solid-liquid separation unit connected in sequence; the reaction tower is also connected to a heat supply unit and an air delivery unit, and the heat exchange unit is connected to the heat supply unit;

[0021] The process steps of the application are as follows:

[0022] Firstly, the residual sludge is transported to the reaction tower by using the raw sludge transmission system, and then the carbon-coated dual-active site nitrogen-doped carbon-based catalyst is added into the reaction tower, an oxidant is introduced into the reaction tower through an air delivery unit, and the reaction tower is heated by using a heat supply unit. The carbon-coated dual-active site nitrogen-doped carbon-based catalyst undergoes a hydrothermal oxidation reaction with the residual sludge, the residual sludge is broken down and a carboxylic acid carbon source is generated, and a solid-liquid mixture material formed after the hydrothermal oxidation reaction is cooled by a heat exchange unit. After cooling, the solid-liquid mixture material enters a solid-liquid separation unit for solid-liquid separation, and the separated supernatant and filter cake resources are collected respectively.

[0023] Furthermore, the conditions of the hydrothermal oxidation reaction are: reaction pressure 1.0-5.0 MPa, reaction temperature 140-200°C, volume space velocity 0.5-2.0 h-1 , the oxidant is oxygen in the air.

[0024] The beneficial effects of the present invention are:

[0025] The present invention discloses a carbon-coated dual-active site nitrogen-doped carbon-based catalyst. Nitrogen doping in the catalyst carrier can form a defect structure inside the carbon material, provide abundant acid-base sites for the catalyst, thereby improving the oxidation reaction activity, and further improving the degree of decomposition of sludge extracellular polymers, so that more organic matter in the sludge enters the sludge liquid phase, making the sludge decomposition more thorough, and improving the selectivity of organic carboxylic acid products; the metal particles on the surface of the catalyst can further improve the catalytic activity, promote the generation of active oxygen species, and achieve efficient carbon chain reforming during the reaction process. The defect structure inside the catalyst can also effectively promote the transfer of electrons to the active metal, accelerate the adsorption and activation of the reactant molecules; at the same time, the degree of oxidation can be controlled through the synergistic effect between the defect structure and the active metal, and the C1-C2 carboxylic acid products can be improved. Selectivity; the defect structure can provide anchoring points for active metals, improve the coordination morphology of transition metal species, and make active metals not easily lost during the hydrothermal process. Moreover, the carbon-coated structure on the outside of the catalyst can provide protection for the active metals without affecting the activation of the oxidant, so that they are not affected by complex environmental factors, such as high-salt environment, thereby improving the stability of the catalyst. Moreover, this catalyst can achieve HTO resource treatment of sludge under conditions below 200°C without causing secondary pollution. The carbon-coated dual-active site nitrogen-doped carbon-based catalyst can effectively improve the stability of the catalyst in complex environments, especially in high-salt systems, while ensuring efficient catalytic performance. It can provide an efficient and low-cost treatment solution for HTO treatment sludge resource treatment, and has broad application prospects in the field of organic solid waste resource treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 A schematic diagram of the structure of a device for treating excess sludge using the catalyst prepared by the present invention;

[0028] Figure 2 It is a structural schematic diagram of a small test device used when treating excess sludge using the catalyst prepared in an embodiment of the present invention.

[0029] In the figure:

[0030] 1. Heat supply unit; 2. Reaction tower; 3. Heat exchange unit; 4. Solid-liquid separation unit; 5. Carbon source conveying pipeline; 6. Mud cake transfer vehicle; 7. Air pipeline; 8. Raw sludge transmission pipeline; 9. Cold water pipeline; 10. Heat circulation pipeline; 11. Heating furnace; 12. Reactor; 13. Heat exchanger; 14. Sample storage tank; 15. Air conveying pipeline; 16. Air pressure valve; 17. Gas flow meter; 18. Temperature measuring device; 19. Sampling pipeline; 20. Exhaust pipeline; 21. Vent pipeline; 22. Electronic scale. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The specific principles involved in the present invention are:

[0033] During the preparation process, the various components of the catalyst are in close contact, so that the nitrogen source (N) is doped in the carbon-based (C) structure. Since N atoms have a smaller atomic radius and a greater electronegativity than C atoms, defects appear in the C structure. The active metal enters the C structure during the preparation process and successfully occupies the formed C defect structure. Finally, the active metal in the catalyst is anchored by high-temperature calcination.

[0034] Through the synergistic effect between the C structural defects caused by N doping and the active metals, on the one hand, electron transfer is improved, the efficiency of the generation of oxygen-containing free radicals is increased, the degree of decomposition of extracellular polymers of sludge is improved, the sludge decomposition efficiency is improved, and the selectivity of organic carboxylic acid products is improved. On the other hand, the degree of oxidation is controlled through the synergistic effect between the structure and the active metals, and the selectivity of the reaction products is further improved. At the same time, the anchoring of the metal in the defective structure and the structure of a layer of carbon film coated on the carbon ball provide dual protection for the catalyst, thereby improving the stability of the catalyst in complex environments (such as high salt).

[0035] Example

[0036] Embodiment 1:

[0037] The carbon-coated dual-active site nitrogen-doped carbon-based catalyst FeNi@CN / C-1 was prepared by an in-situ synthesis method, comprising the following steps:

[0038] 25g of ferric nitrate and 2.5g of nickel nitrate were dissolved in 110mL of deionized water to obtain a mixed solution, 100g of waste resin was added to the mixed solution, 250g of nitrogen source urea was added to the solution and ultrasonicated for 30min, and the obtained mixture after ultrasonication was dried at 103-105°C for 6h. The dried product was calcined at 850°C for 2h in a nitrogen atmosphere, the temperature program was set to 3°C / min, and the catalyst FeNi@CN / C-1 was prepared after natural cooling, with an Fe content of 5wt%, a mass ratio of Fe to Ni of 10:1, and a thickness of the catalyst carbon coating layer of 0.3nm.

[0039] Embodiment 2:

[0040] The carbon-coated dual-active site nitrogen-doped carbon-based catalyst CuNi@CN / C-1 was prepared by an in-situ synthesis method, comprising the following steps:

[0041] 25g of copper nitrate and 2.5g of nickel nitrate were dissolved in 110mL of deionized water to obtain a mixed solution, 100g of waste resin was added to the mixed solution, 250g of nitrogen source urea was added to the solution and ultrasonicated for 30min, and the obtained mixture after ultrasonication was dried at 103-105°C for 6h. The dried product was calcined at 850°C for 2h in a nitrogen atmosphere, the temperature program was set to 3°C / min, and the catalyst CuNi@CN / C-1 was prepared after natural cooling, with a Cu content of 5wt%, a Cu to Ni mass ratio of 10:1, and a catalyst carbon coating layer thickness of 0.3nm.

[0042] Embodiment 3:

[0043] The carbon-coated dual-active site nitrogen-doped carbon-based catalyst MnNi@CN / C-1 was prepared by an in-situ synthesis method, comprising the following steps:

[0044] 25g of manganese nitrate and 2.5g of nickel nitrate were dissolved in 110mL of deionized water to obtain a mixed solution, 100g of waste resin was added to the mixed solution, 250g of nitrogen source urea was added to the solution and ultrasonicated for 30min, and the mixture obtained after ultrasonication was dried at 103-105°C for 6h. The dried product was calcined at 850°C for 2h in a nitrogen atmosphere, the temperature program was set to 3°C / min, and the catalyst MnNi@CN / C-1 was prepared after natural cooling, with a Mn content of 5wt%, a mass ratio of Fe to Ni of 10:1, and a thickness of the catalyst carbon coating layer of 0.3nm.

[0045] Example 4

[0046] The carbon-coated dual-active site nitrogen-doped carbon-based catalyst FeNi@CN / C-2 was prepared by an in-situ synthesis method, comprising the following steps:

[0047] 15g of ferric nitrate and 1.5g of nickel nitrate were dissolved in 110mL of deionized water to obtain a mixed solution, 100g of waste resin was added to the mixed solution, 250g of nitrogen source urea was added to the solution and ultrasonicated for 30min, and the obtained mixture after ultrasonication was dried at 103-105°C for 6h. The dried product was calcined at 650°C for 2h under a nitrogen atmosphere, the temperature program was set to 3°C / min, and the catalyst FeNi@CN / C-2 was prepared after natural cooling, with an Fe content of 2.5wt%, a mass ratio of Fe to Ni of 10:1, and a thickness of the catalyst carbon coating layer of 0.3nm.

[0048] Embodiment 5:

[0049] The carbon-coated dual-active site nitrogen-doped carbon-based catalyst FeNi@CN / C-3 was prepared by an in-situ synthesis method, comprising the following steps:

[0050] 25g of ferric nitrate and 1.25g of nickel nitrate were dissolved in 110mL of deionized water to obtain a mixed solution, 100g of waste resin was added to the mixed solution, 250g of nitrogen source urea was added to the solution and ultrasonicated for 30min, and the obtained mixture after ultrasonication was dried at 103-105°C for 6h. The dried product was calcined at 1000°C for 2h in a nitrogen atmosphere, the temperature program was set to 3°C / min, and the catalyst FeNi@CN / C-3 was prepared after natural cooling, with an Fe content of 5wt%, a mass ratio of Fe to Ni of 20:1, and a thickness of the catalyst carbon coating layer of 0.3nm.

[0051] Embodiment 6:

[0052] The carbon-coated dual-active site nitrogen-doped carbon-based catalyst FeNi@CN / C-4 was prepared by an in-situ synthesis method, comprising the following steps:

[0053] 50g of ferric nitrate and 5.0g of nickel nitrate were dissolved in 110mL of deionized water to obtain a mixed solution, 100g of waste resin was added to the mixed solution, 250g of nitrogen source urea was added to the solution and ultrasonicated for 30min, and the obtained mixture after ultrasonication was dried at 103-105°C for 6h. The dried product was calcined at 850°C for 2h in a nitrogen atmosphere, the temperature program was set to 3°C / min, and the catalyst FeNi@CN / C-4 was prepared after natural cooling, with an Fe content of 7.5wt%, a mass ratio of Fe to Ni of 10:1, and a thickness of the catalyst carbon coating layer of 0.3nm.

[0054] Embodiment 7:

[0055] The carbon-coated dual-active site nitrogen-doped carbon-based catalyst FeNi@CN / C-5 was prepared by an in-situ synthesis method, comprising the following steps:

[0056] 100g of ferric nitrate and 10g of nickel nitrate were dissolved in 110mL of deionized water to obtain a mixed solution, 100g of waste resin was added to the mixed solution, 500g of nitrogen source urea was added to the solution and ultrasonicated for 30min, and the obtained mixture after ultrasonication was dried at 103-105°C for 6h. The dried product was calcined at 850°C for 2h under a nitrogen atmosphere, the temperature program was set to 3°C / min, and the catalyst FeNi@CN / C-5 was prepared after natural cooling, with an Fe content of 10wt%, a mass ratio of Fe to Ni of 10:1, and a thickness of the catalyst carbon coating layer of 0.3nm.

[0057] Embodiment 8:

[0058] The carbon-coated dual-active site nitrogen-doped carbon-based catalyst FeNi@CN / C-6 was prepared by an in-situ synthesis method, comprising the following steps:

[0059] 5g of ferric nitrate and 0.5g of nickel nitrate were dissolved in 110mL of deionized water to obtain a mixed solution, 100g of waste resin was added to the mixed solution, 100g of nitrogen source urea was added to the solution and ultrasonicated for 30min, and the obtained mixture after ultrasonication was dried at 103-105°C for 6h. The dried product was calcined at 850°C for 2h under a nitrogen atmosphere, the temperature program was set to 3°C / min, and the catalyst FeNi@CN / C-6 was prepared after natural cooling, with an Fe content of 1wt%, a mass ratio of Fe to Ni of 10:1, and a thickness of the catalyst carbon coating layer of 0.3nm.

[0060] Comparative Example

[0061] Comparative Example 1:

[0062] The Fe@C catalyst was prepared by a common impregnation method, comprising the steps of: dissolving 25 g of ferric nitrate in 110 mL of deionized water to obtain a mixed solution, taking 100 g of waste resin and adding it to the mixed solution, ultrasonicating for 30 minutes, and drying the mixture obtained after ultrasonicating at a temperature of 103-105° C. for 6 hours. The dried product was calcined at 850° C. for 2 hours under a nitrogen atmosphere, the temperature program was set to 3° C. / min, and the catalyst Fe@C was prepared after natural cooling, and the Fe content was 5wt%.

[0063] 1. Performance test:

[0064] Evaluate catalyst effects and reaction conditions through laboratory tests

[0065] 1. Laboratory test device: Figure 2 The 200 mL fixed bed reactor (model: CWAO-DA480) shown was developed by the Dalian Institute of Chemical Physics, Chinese Academy of Sciences. The process can be scaled up proportionally;

[0066] 2. The pilot test process is as follows: first, the catalyst is put into the reactor, and then the remaining sludge is transported to the fixed bed reactor through a high-pressure sludge pump, air is introduced into the reactor through an air delivery unit (a selection valve, a pressure relief valve, and a gas flow regulating valve are provided on the air delivery pipeline), and the heat source required for the reaction is provided to the reactor through a heating furnace. The catalyst and the remaining sludge undergo hydrolysis and oxidation reactions in the reactor, and the material obtained after the reaction is cooled by a heat exchanger, and the cooled solid-liquid mixture enters a sample storage tank, and finally the solid-liquid mixture in the sample storage tank is separated and filtered by a solid-liquid separation unit, and the supernatant obtained is the carboxylic acid carbon source;

[0067] 3. Catalyst evaluation method: The carbon-coated dual-active site nitrogen-doped carbon-based catalyst prepared in Example 1 to Example 8 was used to treat the residual sludge. At the same time, the reaction without adding catalyst was used as the control group, and the catalyst evaluation test was performed in the HTO laboratory test. 200 mL of catalyst was added, and the sludge pump was used for sampling. Air was introduced as an oxidant. The reaction temperature was set to 180°C, the reaction pressure was set to 2.0 MPa, and the reaction contact time was set to 1.0 h (volume space velocity 1.0 h -1 ) After the first 8 hours of sample release, samples were taken every 6 hours. Each condition was sampled 3 times and the results were averaged.

[0068] Catalyst evaluation result analysis method: After the reaction, the sample was filtered, and the supernatant was tested for soluble COD using the national standard method and VFAs using high performance liquid chromatography; the mud cake was tested for moisture content, TS, and VS. The sample was refrigerated and stored at 4°C.

[0069] 4. Catalyst evaluation results:

[0070] The FeNi@CN / C-1 catalyst prepared in Example 1 was used to treat municipal sludge (TS was 23.2 mg / L, VS was 15.9 mg / L). After HTO treatment, the COD of the sludge pyrolysis liquid was 10001 mg / L, and oxalic acid 3101 mg / L (COD 551.1 mg / L), pyruvic acid 219 mg / L (COD 198.9 mg / L), glycolic acid 1015 mg / L (COD 640.6 mg / L), lactic acid 2481 mg / L (COD 2643.9 mg / L), formic acid 287 mg / L (COD 99.8 mg / L), and acetic acid 5449 mg / L (COD 5806.9 mg / L) were detected in the pyrolysis liquid. The contribution of carboxylic acid to COD was 99.4%, of which acetic acid accounted for the highest proportion of over 58.1%. After the reaction, the VS / TS of the sludge dropped from 0.69 to 0.094, indicating that the prepared catalyst had good activity and a high degree of decomposition of sludge extracellular polymers, allowing more organic matter in the sludge to enter the sludge liquid phase, making the sludge decomposition more thorough, achieving deep sludge decomposition, and extremely high selectivity for carboxylic acid products.

[0071] The CuNi@CN / C-1 catalyst prepared in Example 2 was used to treat municipal sludge (TS was 23.2 mg / L, VS was 15.9 mg / L). After HTO treatment, the COD of the sludge pyrolysis liquid was 10494 mg / L, and oxalic acid 2661 mg / L (COD 472.9 mg / L), maleic acid 57.8 mg / L (COD 47.8 mg / L), pyruvic acid 226 mg / L (COD 205.6 mg / L), glycolic acid 1315 mg / L (COD 829.9 mg / L), lactic acid 1889 mg / L (COD 2013.0 mg / L), formic acid 555 mg / L (COD 192.9 mg / L), and acetic acid 5789 mg / L (COD 6169.2 mg / L) were detected in the pyrolysis liquid. The selectivity of carboxylic acids was 94.6%, of which acetic acid accounted for the highest proportion of over 58.8%. The VS / TS of the filter cake after HTO treatment dropped from 0.69 to 0.097, indicating that the prepared catalyst had good activity and a high degree of decomposition of extracellular polymers in the sludge, allowing more organic matter in the sludge to enter the sludge liquid phase, making the sludge decomposition more thorough, achieving deep sludge decomposition, and extremely high selectivity for carboxylic acid products.

[0072] The MnNi@CN / C-1 catalyst prepared in Example 3 was used to treat municipal sludge (TS was 23.2 mg / L, VS was 15.9 mg / L). After HTO treatment, the COD of the sludge pyrolysis liquid was 10025 mg / L, and oxalic acid 3010 mg / L (COD 534.9 mg / L), maleic acid 58.2 mg / L (COD 48.1 mg / L), pyruvic acid 198 mg / L (COD 179.9 mg / L), glycolic acid 1111 mg / L (COD 701.2 mg / L), lactic acid 2001 mg / L (COD 2132.4 mg / L), formic acid 467 mg / L (COD 162.3 mg / L), and acetic acid 5479 mg / L (COD 5838.8 mg / L) were detected in the pyrolysis liquid. The selectivity of carboxylic acids was 95.7%, of which acetic acid accounted for the highest proportion of over 58.2%. The VS / TS of the filter cake after HTO treatment dropped from 0.69 to 0.098, indicating that the prepared catalyst had good activity and a high degree of decomposition of extracellular polymers in the sludge, allowing more organic matter in the sludge to enter the sludge liquid phase, making the sludge decomposition more thorough, achieving deep sludge decomposition, and extremely high selectivity for carboxylic acid products.

[0073] The FeNi@CN / C-2 catalyst prepared in Example 4 was used to treat municipal sludge (TS was 23.2 mg / L, VS was 15.9 mg / L). After HTO treatment, the COD of the sludge pyrolysis liquid was 9826 mg / L, and oxalic acid 2999 mg / L (COD 532.9 mg / L), pyruvic acid 222 mg / L (COD 201.7 mg / L), glycolic acid 1020 mg / L (COD 643.7 mg / L), lactic acid 2551 mg / L (COD 2718.5 mg / L), formic acid 198 mg / L (COD 68.8 mg / L), and acetic acid 5201 mg / L (COD 5542.6 mg / L) were detected in the pyrolysis liquid. The selectivity of carboxylic acids is 98.8%, among which acetic acid accounts for the highest proportion of over 56.4%. The VS / TS of the filter cake after HTO treatment is reduced from 0.69 to 0.096, indicating that the prepared catalyst has good activity and a high degree of decomposition of extracellular polymers in the sludge, allowing more organic matter in the sludge to enter the sludge liquid phase, making the sludge decomposition more thorough, achieving deep sludge decomposition, and extremely high selectivity for carboxylic acid products.

[0074] Using the FeNi@CN / C-3 catalyst prepared in Example 5, the COD of the sludge pyrolysis liquid after HTO treatment was 9992 mg / L, and oxalic acid 3569 mg / L (COD 634.2 mg / L), pyruvic acid 500 mg / L (COD 454.2 mg / L), glycolic acid 1279 mg / L (COD 807.2 mg / L), lactic acid 2117 mg / L (COD 2256 mg / L), formic acid 256 mg / L (COD 89.0 mg / L), and acetic acid 4466 mg / L (COD 4759.3 mg / L) were detected in the pyrolysis liquid. The selectivity of carboxylic acids was 90.1%, of which acetic acid accounted for the highest proportion of over 47.6%. The VS / TS of the filter cake after HTO treatment dropped from 0.69 to 0.096, indicating that the prepared catalyst had good activity and a high degree of decomposition of extracellular polymers in the sludge, allowing more organic matter in the sludge to enter the sludge liquid phase, making the sludge decomposition more thorough, achieving deep sludge decomposition, and extremely high selectivity for carboxylic acid products.

[0075] The FeNi@CN / C-4 catalyst prepared in Example 6 was used to treat municipal sludge (TS was 23.2 mg / L, VS was 15.9 mg / L). After HTO treatment, the COD of the sludge pyrolysis liquid was 9998 mg / L, and oxalic acid 2089 mg / L (COD 371.2 mg / L), pyruvic acid 186 mg / L (COD 169.0 mg / L), glycolic acid 672 mg / L (COD 424.1 mg / L), lactic acid 2154 mg / L (COD 2295.4 mg / L), formic acid 177 mg / L (COD 61.5 mg / L), and acetic acid 5721 mg / L (COD 6096.7 mg / L) were detected in the pyrolysis liquid. The contribution of carboxylic acid to COD was 94.2%, of which acetic acid accounted for the highest proportion of over 61.0%. After the reaction, the VS / TS of the sludge dropped from 0.69 to 0.096, indicating that the prepared catalyst has good activity and a high degree of decomposition of sludge extracellular polymers, allowing more organic matter in the sludge to enter the sludge liquid phase, making the sludge decomposition more thorough, achieving deep sludge decomposition, and has extremely high selectivity for carboxylic acid products.

[0076] The FeNi@CN / C-5 catalyst prepared in Example 7 was used to treat municipal sludge (TS was 23.2 mg / L, VS was 15.9 mg / L). After HTO treatment, the COD of the sludge pyrolysis liquid was 8624 mg / L, and oxalic acid 1567 mg / L (COD 278.5 mg / L), pyruvic acid 88 mg / L (COD 79.9 mg / L), glycolic acid 678 mg / L (COD 427.9 mg / L), lactic acid 1850 mg / L (COD 1971.5 mg / L), formic acid 29 mg / L (COD 10.1 mg / L), and acetic acid 5002 mg / L (COD 5330.5 mg / L) were detected in the pyrolysis liquid. The contribution of carboxylic acid to COD was 93.9%, of which acetic acid accounted for the highest proportion of over 61.8%. After the reaction, the VS / TS of the sludge dropped from 0.69 to 0.094, indicating that the prepared catalyst has good activity and a high degree of decomposition of sludge extracellular polymers, allowing more organic matter in the sludge to enter the sludge liquid phase, making the sludge decomposition more thorough, achieving deep sludge decomposition, and extremely high selectivity for carboxylic acid products.

[0077] The FeNi@CN / C-6 catalyst prepared in Example 8 was used to treat municipal sludge (TS was 23.2 mg / L, VS was 15.9 mg / L). After HTO treatment, the COD of the sludge pyrolysis liquid was 9237 mg / L, and oxalic acid 1122 mg / L (COD 199.4 mg / L), pyruvic acid 89 mg / L (COD 80.8 mg / L), glycolic acid 894 mg / L (COD 564.2 mg / L), lactic acid 2870 mg / L (COD 3058.4 mg / L), formic acid 68 mg / L (COD 23.6 mg / L), and acetic acid 4121 mg / L (COD 4391.7 mg / L) were detected in the pyrolysis liquid. The contribution of carboxylic acid to COD was 90.1%, of which acetic acid accounted for the highest proportion of over 47.5%. After the reaction, the VS / TS of the sludge dropped from 0.69 to 0.097, indicating that the prepared catalyst has good activity and a high degree of decomposition of sludge extracellular polymers, allowing more organic matter in the sludge to enter the sludge liquid phase, making the sludge decomposition more thorough, achieving deep sludge decomposition, and extremely high selectivity for carboxylic acid products.

[0078] In the control group, after 97% municipal sludge was treated with HTO by unadded carbon-coated dual-active site nitrogen-doped carbon-based catalyst, the COD of the sludge pyrolysis liquid was 8339 mg / L, and oxalic acid 20.1 mg / L, pyruvic acid 13.4 mg / L, glycolic acid 585.2 mg / L, formic acid 262.3 mg / L, acetic acid 316.9 mg / L, propionic acid 1165.9 mg / L, butyric acid 653.8 mg / L, isovaleric acid 214 mg / L were detected, and the contribution of carboxylic acid COD accounted for 50.4%. After the reaction, the sludge VS / TS dropped from 0.69 to 0.59.

[0079] It can be seen that under the same conditions, compared with the dual-active site nitrogen-doped carbon-based catalyst without adding carbon coating, the use of the catalyst prepared in Example 1 to Example 8 to treat sludge can not only increase the COD of the sludge pyrolysis liquid, reduce VS / TS, improve the degree of decomposition of sludge extracellular polymers, improve the decomposition effect of sludge, release more organic matter, and achieve deep decomposition of sludge, but also can increase the carboxylic acid selectivity from 50.4% to more than 90%, which is beneficial to the subsequent resource utilization of the pyrolysis liquid as a composite carbon source of carboxylic acids.

[0080] 5. Reaction condition evaluation method: Take the catalyst prepared in Example 1 for HTO test, and carry out HTO test in the above-mentioned 10-hour device to examine the reaction temperature (140-200°C), reaction pressure (1.0-5.0MPa), reaction contact time (volume space velocity 0.5-2.0h -1 )’s impact.

[0081] Reaction condition evaluation result analysis method: After the reaction, the sample was filtered, and the supernatant was tested for soluble COD using the national standard method and VFAs using high performance liquid chromatography; the mud cake was tested for moisture content, TS, and VS. The sample was refrigerated and stored at 4°C.

[0082] 6. Reaction condition evaluation results:

[0083] (1) Effect of reaction pressure

[0084] Reaction temperature 180℃, reaction contact time 1.0h (volume space velocity 1.0h -1 ), the reaction pressure was set to 1.0, 2.0, 3.0, 4.0, and 5.0 MPa respectively, and the results are as follows:

[0085]

[0086] From the above results, it can be seen that within the range of 1.0-5.0MPa, the sludge is well broken down, the organic matter is well released, and more than 99% of the pollutants are converted into carboxylic acid products, which is beneficial for subsequent application as a carbon source. The increase in reaction pressure is beneficial to the deep breakdown of sludge and the removal of organic pollutants, which is beneficial to reducing the VS / TS of sludge after treatment and improving the degree of stabilization. However, with the increase in pressure, the oxidation capacity is enhanced, and the degree of complete mineralization of pollutants becomes higher, resulting in a decrease in the proportion of carboxylic acid COD in the pyrolysis solution.

[0087] (2) Effect of reaction temperature

[0088] Reaction pressure 2.0MPa, volume space velocity 1.0h -1 , the reaction temperatures were set at 140, 160, 180, and 200°C, respectively. The results are as follows:

[0089]

[0090] From the above results, it can be seen that within the range of 140-200°C, the sludge is well broken down, the organic matter is well released, and more than 99% of the pollutants are converted into carboxylic acid products, which is beneficial for subsequent application as a carbon source. The increase in reaction temperature is conducive to the deep breakdown of sludge and the removal of organic pollutants, which is beneficial to reducing the VS / TS of sludge after treatment and improving the degree of stabilization. However, as the temperature increases, the oxidation capacity increases, and the degree of complete mineralization of pollutants increases, resulting in a decrease in the proportion of carboxylic acid COD in the pyrolysis solution.

[0091] (3) Effect of reaction contact time

[0092] The reaction pressure was 2.0 MPa, the reaction temperature was 180°C, and the volumetric space velocity was set to 0.5 h -1 , 1.0h -1 , 2.0h-1 , that is, the reaction contact time is 2.0, 1.0, and 0.5h, and the results are as follows:

[0093]

[0094] From the above results, it can be seen that within the range of 0.5 to 2.0 h of reaction contact time, the sludge is well broken down, the organic matter is well released, and more than 99% of the pollutants are converted into carboxylic acid products, which is beneficial for subsequent application as a carbon source. The extension of the reaction contact time is beneficial to the deep breakdown of the sludge and the removal of organic pollutants, which is beneficial to reduce the VS / TS of the sludge after treatment and improve the degree of stabilization. However, as the contact time increases, the degree of oxidation becomes deeper, and the degree of complete mineralization of the pollutants becomes higher, resulting in a decrease in the proportion of carboxylic acid COD in the pyrolysis solution. A shorter reaction contact time will lead to incomplete sludge breakdown, resulting in a higher VS / TS.

[0095] 7. Catalyst performance test in high salt system:

[0096] The catalyst prepared in Example 1 and the Fe@C catalyst prepared in Comparative Example 1 were tested by simulating the treatment of residual sludge in a high-salt system.

[0097] (1) The specific method is:

[0098] 5 wt.% of Cl ions were added to the reaction substrate municipal sludge (TS was 23.2 mg / L, VS was 15.9 mg / L) to simulate a high salt system, and the FeNi@CN / C-1 catalyst prepared in Example 1 and the Fe@C catalyst prepared in Comparative Example 1 were used to carry out HTO continuous reaction, and the device, reaction process, catalyst evaluation method and catalyst evaluation result analysis method used were the same as those in 1, 2 and 3 above;

[0099] (2) Results

[0100] After treating the sludge with HTO in a high salt system using the FeNi@CN / C-1 catalyst prepared in Example 1, the COD in the sludge pyrolysis liquid was 10587 mg / L, and oxalic acid 1988 mg / L (COD 353.3 mg / L), pyruvic acid 226 mg / L (COD 205.6 mg / L), glycolic acid 1125 mg / L (COD 710.0 mg / L), lactic acid 2000 mg / L (COD 2131.3 mg / L), formic acid 267 mg / L (COD 92.8 mg / L), acetic acid 4999 mg / L (COD 5327.3 mg / L), and propionic acid 657 mg / L (COD 993.2 mg / L) were detected in the pyrolysis liquid. The selectivity of carboxylic acids is 92.3%, of which acetic acid accounts for the highest proportion of over 50.3%. The VS / TS of the filter cake after HTO treatment is reduced from 0.69 to 0.101. It can be seen that the high salt system has no obvious effect on the catalytic effect.

[0101] 5 wt.% of Cl ions were added to the reaction substrate sludge (same as in Example 1) to simulate a high salt system, and the Fe@C catalyst prepared in Comparative Example 1 was added to carry out HTO intermittent reaction. The method, detection index and detection method were the same as in Example 1;

[0102] Results: COD of sludge pyrolysis liquid after HTO treatment was 8339mg / L, oxaloacetic acid 556mg / L (COD350.9mg / L), formic acid 114mg / L (COD 39.6mg / L), acetic acid 276mg / L (COD 294.1mg / L), propionic acid 1335mg / L (COD 2018.2mg / L), butyric acid 649mg / L (COD 1178.5mg / L), isoacid 225mg / L (COD 458.2mg / L), carboxylic acid COD contribution accounted for 49.7%. After the reaction, the sludge VS / TS dropped from 0.69 to 0.60.

[0103] It can be seen that the high-salt environment has a more obvious effect on the activity of the Fe@C catalyst, while it can be seen from Example 6 that the activity of FeNi@CN / C-1 in a high-salt system is not affected, indicating that the carbon-coated structure of the HTO catalyst provided in this invention provides protection for the catalyst, enabling it to maintain catalytic activity in a high-salt environment.

[0104] 2. Process testing:

[0105] The process of the process test of using the carbon-coated dual-active site nitrogen-doped carbon-based catalyst prepared by the present invention to treat excess sludge and simultaneously prepare a carboxylic acid carbon source is as follows:

[0106] like Figure 1The figure shows the structure of the device used when the catalyst prepared by the present invention is used to treat excess sludge. The reaction tower 2 is connected to the heat exchange unit 3, the heat exchange unit is connected to the solid-liquid separation unit 4, the heat supply unit 1 (boiler) is connected to the reaction tower 2, and the heat exchange unit 3 is connected to the heat supply unit 1 (boiler); firstly, the catalyst is put into the reaction tower of the device, the excess sludge is transported to the reaction tower through the biological material transport unit, air is introduced into the reaction tower through the air transport unit, the heat source required for the reaction is provided to the reaction tower through the heat supply unit, and the catalyst and the excess sludge undergo a hydrothermal oxidation reaction. The remaining sludge is effectively broken down. The material obtained after the reaction is cooled by the heat exchange unit. The heat generated by the cooling of the reactants is recovered by the heat exchange unit and transported to the heat supply unit to achieve heat recovery and circulation. The cooled material is separated by the solid-liquid separation unit, and the supernatant obtained is the carboxylic acid carbon source, which can be used as a composite carbon source in the process of sewage treatment to achieve resource utilization. The main inorganic components of the solid mud cake obtained are oxides of silicon, aluminum, calcium, iron, etc. and trace heavy metals, which can be used as inorganic fillers for packaging cardboard, and can also be fired into ceramsite and catalysts for further resource utilization.

[0107] The FeNi@CN / C-1 catalyst prepared in Example 1 was selected and Figure 1 In the process shown, the process test of HTO resource treatment of municipal sludge was carried out, the reaction temperature was 180°C, the reaction pressure was 2.0MPa, the reaction contact time was 1.0h, and the sludge from the sewage treatment plant was treated in situ (sludge moisture content 98%±1%). Since the properties of daily sludge (such as pollution degree, distribution of pollutants contained, etc.) change according to the actual daily sewage treatment conditions, the VS / TS of the sludge after treatment is between 0.095 and 0.130, and the COD of the pyrolysis liquid is above 10000mg / L and below 20000mg / L, of which carboxylic acid products account for more than 90%, up to 99.9%, and the main products are C2~C4 monoacids and diacids. There are no biologically toxic by-products in the pyrolysis liquid after sludge treatment, and it can be used as a high-quality carbon source.

[0108] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A carbon-coated dual-active site nitrogen-doped carbon-based catalyst, characterized in that: The catalyst comprises two active metal-supported nitrogen-doped carbon spheres and a carbon coating layer; The metal active component includes a first metal and a second metal, wherein the first metal is one of transition metals Fe, Mn, and Cu, and the second metal is metal Ni.

2. A carbon-coated dual-active site nitrogen-doped carbon-based catalyst according to claim 1, characterized in that: The loading amount of the first metal is 1 to 10 wt %; The mass ratio of the first metal to the second metal is 10 to 20:

1.

3. A carbon-coated dual-active site nitrogen-doped carbon-based catalyst according to claim 1, characterized in that: The carrier precursor of the nitrogen-doped carbon spheres is waste resin.

4. A method for preparing a carbon-coated dual-active site nitrogen-doped carbon-based catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: dissolving 10-50 g of a nitrate containing a first metal and 1-10 g of a nitrate containing a second metal in 110 mL of deionized water to obtain a mixed solution, adding 100 g of waste resin as a precursor to the mixed solution, then adding a nitrogen source, and ultrasonicating for 15-30 min to obtain a mixture; S2: The mixture after ultrasound was dried, calcined and naturally cooled to obtain a carbon-coated dual-active site nitrogen-doped carbon-based catalyst.

5. The preparation method according to claim 4, characterized in that: The nitrogen source is selected from at least one of urea and dicyandiamide powder, and the mass ratio of the nitrogen source to the waste resin precursor is 1 to 5:

1.

6. The preparation method according to claim 4, characterized in that: In S2, the drying condition is: drying at a temperature of 103-105° C. for 3-6 hours.

7. The preparation method according to claim 4, characterized in that: In S2, the calcination conditions are: the dried product is calcined at 600-1000°C for 2h under an inert atmosphere, and the temperature program is set at 1-5°C / min.

8. Use of a carbon-coated dual-active site nitrogen-doped carbon-based catalyst as described in any one of claims 1 to 3 or a carbon-coated dual-active site nitrogen-doped carbon-based catalyst prepared by the preparation method as described in any one of claims 4 to 7 in treating excess sludge to produce carboxylic acid carbon sources.

9. The use according to claim 8, characterized in that: The application is carried out in a device for hydrothermal oxidation of excess sludge, the device for hydrothermal oxidation of excess sludge comprising a raw sludge transmission system, a reaction tower (2), a heat exchange unit (3) and a solid-liquid separation unit (4) connected in sequence; the reaction tower (2) is also connected to a heat supply unit (1) and an air delivery unit, and the heat exchange unit (3) is connected to the heat supply unit (1); The process steps of the application are as follows: First, the residual sludge is transported to the reaction tower (2) by using a raw sludge transport system, and then the carbon-coated dual-active site nitrogen-doped carbon-based catalyst is added to the reaction tower (2), and an oxidant is introduced into the reaction tower (2) through an air transport unit. The reaction tower (2) is heated by using a heat supply unit (1). The carbon-coated dual-active site nitrogen-doped carbon-based catalyst catalyzes the residual sludge to undergo a hydrothermal oxidation reaction, and the residual sludge is broken down to generate a carboxylic acid carbon source. The solid-liquid mixture formed after the hydrothermal oxidation reaction is cooled by a heat exchange unit (3). After the cooling is completed, the solid-liquid mixture enters a solid-liquid separation unit (4) for solid-liquid separation, and the separated supernatant and filter cake resources are collected respectively.

10. The use according to claim 9, characterized in that: The conditions of the hydrothermal oxidation reaction are: reaction pressure 1.0-5.0 MPa, reaction temperature 140-200°C, volume space velocity 0.5-2.0 h -1 , the oxidant is oxygen in the air.